Action spectrum of melanoblast maturation and involvement of the aryl hydrocarbon receptor. (August 2016) - Nakamura, Motoki; Nishida, Emi; Morita, Akimichi
Abstract: The aryl hydrocarbon receptor (AHR) mediates melanocyte activation and skin tanning. We hypothesized that the AHR also mediates melanoblast‐to‐melanocyte maturation. In a cloned cell line, NCCmelb4, derived from mouse neural crest cells, we investigated AHR expression in melanoblasts stimulated by UV irradiation and AHR agonists. We irradiated the cells with UV, ranging from 280 to 380 nm in 10‐nm increments, using a multiwavelength irradiation spectral apparatus. Tyrosinase expression significantly increased with bimodal peaks at 310 and 360 nm. Although melanoblast activation peaked 48 hours after irradiation, the most suitable irradiation interval was 24 hours. AHR expression significantly increased at 360 nm, but not at 310 nm. The AHR agonist, VAF347, and water‐soluble tobacco smoke extract induced melanoblast maturation and AHR activation. The culture supernatant derived from the NS47 fibroblast cell line also induced melanoblast maturation and AHR activation. These findings suggest that UV and environmental stimulation of melanoblast‐to‐melanocyte maturation are enhanced via the AHR pathway.